KESIAPSIAGAAN PETUGAS DALAM MENGHADAPI BENCANA (STUDI KASUS DI BADAN PENANGGULANGAN BENCANA DAERAH KABUPATEN NIAS UTARA - Telaumbanua, Ya'adil; Nababan, Donal; Tarigan, Frida Lina; Warouw, Sonny Priajaya; Siagian, Mido Tua; Sitorus, Mido Ester J.; Wandra, Toni (Universitas Pahlawan, 2022)
To analyze the preparedness of officers to face disasters based on the administration of prevention and preparedness and HR preparedness at BPBD, a qualitative study was conducted at BPBD North Nias district, in January-June 2020. The informant of this study was snowball sampling which is part of nonprobability sampling. The objects observed or interviewed were the existing resources in the field of prevention and preparedness, namely 6 people, 1 Head of BPBD, 1 Head of Prevention and Preparedness, 1 Head of Prevention Section, 1 Head of Preparedness Section and 3 members. The data collection process will use interview, observation, and documentation methods. The results showed that the Prevention and Preparedness Policy in pre-disaster was not yet available. Coordination between related agencies was not well implemented, because there was no MOU. BPBD has not carried out monev and reporting, because there are no programmed preparedness activities, it is still limited to monitoring, evaluation and reporting when a disaster is reported per disaster event. The number of BPBD officers is adequate, but in terms of quality it is still not good, because all BPBD officers do not have a disaster education background and the lack of officers has received disaster training. BPBD has not maximally planned the Prevention and Preparedness activity program in disaster management. There needs to be formal coordination between related sectors during pre-disaster times, so that the activities of each agency during a disaster do not overlap in the field. BPBD needs to collaborate with related agencies, such as conducting joint training activities so that disaster management can run effectively and efficiently. SOPs need to be made starting from building organizational structures involved in disaster mitigation, compiling alternative plans by identifying potential obstacles, and ensuring the deadline for implementing the system with existing standards. Monitoring, evaluation and reporting are needed to assess the results obtained as a basis for future decisions. Officers Need to be provided with disaster education and training on an ongoing basis, in the context of developing and enhancing the skills and abilities of officers in carrying out disaster management efforts quickly and precisely. BPBD needs to make good planning and organization included in the BPBD budget, so that all activities that have been set out in the plan can run according to procedures so that all objectives can be achieved.